Desire : 100 of literature's sexiest stories - Frostrup, Mariella (Head Zeus, 2016)
"Strict mistresses, naughty maids, handsome gardeners and disarming strangers; literature is awash with love, sex and desire ... From romance and seduction to downright dirty deeds, here are prize-winners, bestsellers and rising stars, each of whom prove that when it comes to the bedroom, a little fiction goes a long way"--Publisher's description.